Mediações semióticas em práticas sociais de escrita de crianças em processo de alfabetização - Luciana Prazeres Silva (2015)
Which mediations have occurred and what role have they played in the process of teaching written language? This is the central question of our investigation. Although we think this learning process initiates before a child starting to attend school, school teaching can exert a significant interference upon the process. These two premises have their basis on the Historical-cultural approach of the human development by Levi S. Vigotski (1934/1993, 1931/1995), as well as on the studies about written culture and literacy (SOARES, 1998; CASTANHEIRA, 2007; STREET, 1984; ROJO, 2010; SMOLKA, 1993/2000), and recent studies about classrooms as cultural environments (GOMES & MONTEIRO, 2005; GOMES, DIAS & SILVA, 2008; GOMES, FONSECA, DIAS & VARGAS, 2011; CASTANHEIRA, 2004). In order to develop descriptions, analysis and interpretations about semiotic mediations and their role on the development of written language, we analyzed video records of classes taught in the years of 2006, 2007 and 2008 at a Federal Public school of Belo Horizonte. We also analyzed field notes and artifacts created in the classroom. The material used at the present work is part of the database used for the Including different students at adult and children literacy classrooms: similarities and differences a research coordinated by Prof. Maria de Fátima Cardoso Gomes. We have analyzed as well the writing practices at the literacy classroom I taught. The aforementioned presuppositions have allowed us to analyze the peculiarities of the classroom, the interactions between its actors and the relations between the classroom and the bigger context represented by the school. Such presuppositions have also allowed us to assume a dialectic posture while facing the possibilities of building a unique culture for both collective and singular processes of teaching. We have noticed that the writing practices were brought forth by students and teachers in order to adapt themselves to written language in situations of interaction both inside the classrooms, and with people of their familiarity. The interaction among children and that between the children and their teacher pointed to the importance of building sense and meaning to activities such as learning and writing and using written language as a tool to communicate, feel and think about oneself and about the world one lives in. The activities elaborated by the teacher and their usage allowed the interaction among children, the building of semiotic mediations and the opportunity of every student to learn and develop written language. Regarding children, the learning of written language has evolved through long processes that represented moments of both improvement and regression. The ideas of written language, teaching and learning harbored by the teacher might have been one of the factors determining the existence of diversified semiotic mediations among children. Therefore, a meaningful writing learning process was built together by the group of children as well as it was individually built by the peculiarity of each member of the classroom. We consider the meaning of the uses and the functions of the written language as semiotic mediations, more than the intervention of the teacher or that of their peers. So, without creating meaning to what is being learnt, there could be no mental or cultural development for the children, regarding manipulating, proving and using written language.